Ancestor worship in contemporary Japan - I. V. Avdiushenkova (Японские исследования, 2022)
This article examines the transformation of ancestor worship in the context of socio-political and religious conditions and identifies the characteristics of worship in contemporary Japanese society and the changes in the form of practices and functions of this worship occurring today.